Coherent population of magnetic sublevels of state in hydrogenlike uranium by radiative recombination. (26th November 2015) - Tashenov, S; Banaś, D; Beyer, H; Brandau, C; Fritzsche, S; Gumberidze, A; Hagmann, S; Hillenbrand, P-M; Jörg, H; Kojouharov, I; Kozhuharov, Ch; Lestinsky, M; et al.
Abstract: The x-rays emitted in the process of radiative recombination (RR) of quasi-free electrons into excited state of hydrogenlike uranium ion were studied experimentally. Both the RR x-ray and the subsequently emitted x-ray were detected in time-coincidences. The angular distribution of the x-rays varied as a function of the RR x-ray emission direction. This observation revealed the coherent population of magnetic sublevels of the state in the hydrogenlike uranium ion.